Pengaruh Kesadaran Wajib Pajak, Kualitas Pelayanan Pajak dan Sanksi Pajak Terhadap Kepatuhan Wajib Pajak dalam Membayar Pajak Bumi dan Bangunan Perdesaan dan Perkotaan (PBB-P2) - Numberi, Camelia L. (Fakultas Ekonomi dan Bisnis, Universitas Papua, 2023)
The non-achievement of the target of realization of rural and urban land and building tax revenue (PBB-P2) is the background of the problem in this study. This is certainly an important concern because the rural and urban land and building tax (PBB-P2) contributes to local original revenue (PAD). For this reason, there is a need for compliance that taxpayers have in carrying out their tax obligations. This study aims to determine the effect of taxpayer awareness, quality of tax service and tax sanctions on taxpayer compliance per person in Manokwari Regency. The study population is all taxpayer PBB-P2 domiciled in manokwari regency with a total of 1548 taxpayers. The sample in the study used amounted to 94 taxpayers. For data collection techniques using the questionnaire survey method. The analytical tool used in this study is multiple linear regression analysis. Based on the results of the study, it can be concluded that taxpayer awareness and quality of tax service have a significant effect on taxpayer compliance in paying PBB-P2 tax in Manokwari regency. For tax penalties has no influence on taxpayer compliance in paying PBB-P2 tax in Manokwari regency. The coefficient of determination test showed that 39,9 % of taxpayer’s awareness, service quality, tax penalties were able to explain towards taxpayer’s compliance. While the remaining 60,1% was explained byother variables outside of this study.